INITIATING THARIQAH AKADEMIK PROGRAM TO FLOURISH THE QUALITY EDUCATION IN SUMENEP - SHULHAN SHULHAN; Misnatun; Samsul Ar3 (Institut Kariman Wirayudha Sumenep, 2022)
Thariqah Akademik is a moral force that follows Islamic values and human existence on Earth to fulfill the caliph's primary duty. The core spirit carried by the Thariqah Akademik is to ensure that every Muslim can live and carry out activities vigorously without financial barriers while also fulfilling spiritual obligations obediently. This study examines Thariqah Akademik's program concerning the Sumenep government's vision of developing population growth capacity based on educational outcomes. To describe the work activities surrounding the subject, a qualitative method was used. In this study, the researcher used documentation and observation to collect data from the source. The study's findings are as follows: The first is to improve religious understanding and implementation. the second is applied basic science and language illustriousness. These two things are thought to be the best ways to educate a quality Sumenep generation who have the capability of competing globally while upholding noble values and religious norms.